Implementation of Character Education in Shaping Students' Social Attitudes and Behaviors Through History Learning at SMA PGRI 1 Pati - Siswati, Siswati; Utomo, Cahyo Budi; Muntholib, Abdul (Universitas Negeri Semarang, 2021)
This research aims to find out the process of implementation of duties and social responsibilities of students in SMA PGRI 1 Pati, attitude and social behavior of learners when learning history in SMA PGRI 1 Pati, and the problem of implementation of education in form of attitude and social responsibility of learners in SMA PGRI 1 Pati. This research is a qualitative phenomenological research. The Target of this research is the history teacher of SMA PGRI 1 PATI and a student of class X IPS and XI IPS SMA PGRI 1 PATI. Data collection techniques used were observation, documentation, and interview techniques. Test data validity with Source Triangulation data analysis techniques using data reduction, display, reduction in conclusions, and verification. The results of this research are the processes undertaken in the classroom, outside the classroom with customary school rules, and in the classroom with meanings related to the values of existing characters that can shape students' social attitudes and behaviors. Attitudes and social behavior of high school students PGRI 1 PATI can be said to have been good. The constraints experienced by history teachers are government regulations that vary in different and different contexts. Keywords: character education; social attitudes; social behavior; historical learning.